Discovery of hexagonal ternary phase Ti2InB2 and its evolution to layered boride TiB - Junjie Wang (Nature Portfolio, 2019)
Two-dimensional materials are promising for electrochemical storage and conversion, but are somewhat limited in composition. Here the authors use a computational strategy to predict the existence of a layered boride material, which they synthesize and demonstrate prospective for use as an anode material.